The anarchist inquisition : assassins, activists, and martyrs in Spain and France - Bray, Mark (Political activist) (Cornell University Press, 2022)
"The Anarchist Inquisition is a narrative history of the transnational human rights campaigns that emerged in opposition to the Spanish state's brutal repression of the workers movement in the wake of anarchist propaganda by the deed at the turn of the twentieth century"--